Hypomagnesemia and Type-2 Diabetes Mellitus - Karmakar, Pijush; Jahan, Iffat; Islam, Md Zakirul (Eastern Medical College Journal, 2022)
Diabetes mellitus (DM) has been suggested to be the most common metabolic disorder associated with several macrovascular and microvascular complications. Hypomagnesemia has been reported to occur at an increased frequency among patients with type-2 DM. Those who have poor glycemic control and longtime DM are more likely to decrease the blood magnesium (Mg) level. Mg deficit may also coexist with deficiencies of other dietary elements, such as vitamins, calcium (Ca++) and potassium (K+). Despite numerous reports linking hypomagnesemia to chronic diabetic complications, attention to this issue is poor among clinicians. This article reviews the literature on physiology & biochemistry of Mg++ diagnosis and incidence, features, causes, complications and management of hypomagnesemia in patients with type-2 DM. EMCJ. January 2022; 7(1): 26-31